On a 'Mysterious' Case of a Quadratic Hamiltonian - Sakovich, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
We show that one of the five cases of a quadratic Hamiltonian, which were recently selected by Sokolov and Wolf who used the Kovalevskaya-Lyapunov test, fails to pass the Painlevé test for integrability.